Villoglandular papillary adenocarcinoma of the uterine cervix with lymph node metastasis - A case report and review of the literature - Geok, Chin Tan; Mohd Sidik Shiran,; Manickam Swaminathan,; Poo, Ling Ong; Md Ali Siti Aishah,; Mohd Dali Ahmad Zailani Hatta, (Penerbit UKM, 2006)
Villoglandular papillary adenocarcinoma was first described by Young and Scully in 1989 as a distinct entity with the histological features of exophytic growth proliferation, villous and papillary architecture and mild to moderate nuclear atypia. We report one case of villoglandular papillary adenocarcinoma (VGPA) of the uterine cervix with lymph node metastasis and reviewed the clinicopathological features of six other cases reported in the literature. Our patient is the seventh similar reported cases. They ranged in age from 29 to 54 (mean, 41) years. Five had lymphovascular invasion. All except our patient were treated with radical hysterectomy and radiotherapy. She was followed-up for 7 months and unfortunately died due to chest infection